Effect of Window and Hole Pattern Cut-Outs on Design Optimization of 3D Printed Braces - Rizza, Robert; Liu, XueCheng; Anewenter, Vince (Frontiers in Rehabilitation Sciences, 2022)
Background: There are many different Thoracic Lumbar Sacral Orthosis style brace designs available in the market for the correction of scoliosis deformity. Hole cut out patterns, are commonly used in brace designs. These cut-outs may be subdivided into two groups: hole patterns and windows. Hole patterns are an array of holes which are implemented to lighten the weight of a brace and allow for the skin to breathe. Windows provide space for spinal derotation and/or breathing. From an examination of the literature, it appears that a systematic analysis of the effect of these cut-outs on the structural integrity and functionality of the brace has not been undertaken. Furthermore, there is a lack of understanding on the effect of spacing, size and geometry of the cut-outs on the mechanical behavior of the brace. Method of Approach: In this study, Finite Element Analysis is employed to examine the mechanical response of the brace to these cut-outs. Geometry for the Thoracic Lumbar Sacral Orthosis was obtained by scanning an existing brace. A systematic approach was undertaken where cut-out geometry, spacing and size was varied. Various geometries were analyzed for the hole patterns including circle, triangle, diamond, and hexagon. For the window, the geometries considered were circle, trapezoidal and the “bib” geometry. Results: It was found that linear hole patterns do not provide a desirable structural factor safety. Furthermore, the hexagonal cut-out was the best structurally while reducing the weight of the brace the most. The optimal spacing was found to be 12 mm, and the optimal hole surface area was found to be 78.54 mm2. The “bib” shape provided the best structural integrity and generated the lowest amount of deformation. Conclusions: A hexagonal hole pattern should be used with a spacing of 12 mm and each hole should have a surface area of 78.54 mm2. Windows in the abdominal area should be of “bib” shape. The size of the window cut-outs does not affect the brace stress and deformation significantly.